Pembelajaran Sejarah melalui Metode Karyawisata untuk Meningkatkan Kesadaran Sejarah Bagi Mahasiswa Pendidikan Sejarah FKIP Unbari - Siti Heidi Karmela (Universitas Batanghari Jambi, 2021)
This research is a historical research with a qualitative approach, the main problem is the method of historical field trips to increase learning motivation and historical awareness of the History students, FKIP Unbari. The formulation of the problem proposed is why the method of field trips to historical sites can increase learning motivation and awareness of student history and how students can utilize historical sites that are visited as sources of historical learning. The purpose of this research is to explain the relationship between the field trip method and the increase in student motivation and historical awareness, and describe the function of the historical sites visited through the field trip method for students. Furthermore, the method used is the historical method, consists of heuristic stages (collection of sources), criticism (source verification becomes the primary source and secondary sources), interpretation (the relationship of all sources and give sorurce assessment), and historiography (final writing of research). The conclusion of the research is that the variation of methods when studying history is one aspect that lecturers must pay attention to in order to achieve an active, creative, effective, and enjoyable learning goal (PAKEM). Therefore, if students undergo saturation and boredom during studying in the classroom, lecturers must be dare to try innovative learning methods such as the field trip method by visiting historical sites according to the material in a particular subject.